'Your Tube': the role of different diets in children who are gastrostomy fed: protocol for a mixed methods exploratory sequential study. Issue 10 (9th October 2019) - Taylor, Johanna; O'Neill, Mark; Maddison, Jane; Richardson, Gerry; Hewitt, Catherine; Horridge, Karen; Cade, Janet; McCarter, Alison; Beresford, Bryony; Fraser, Lorna Katharine
Abstract : Introduction: Increasing numbers of children require having all, or part, of their nutritional intake via gastrostomy. More parents are using home-blended meals to feed their children, with many reporting beneficial effects such as improved gastro-oesophageal reflux, less constipation and less distress in their child. This study aims to identify the important outcomes of tube feeding in this population, compare the safety, outcomes and resource use of those on a home-blended diet compared with a formula diet and assess feasibility of long-term follow-up of children recruited to this study. Methods and analyses: This is a mixed methods study of children (aged 6 months to 18 years) who are gastrostomy feed dependent recruited via general, community and specialist paediatric and dietetic services. Workstream 1 ( WS1 ): a qualitative study involving semistructured interviews with parents (n~20) and young people (n~5–10), and focus groups with health professionals (n~25), will provide evidence of appropriate outcome measures and the feasibility/acceptability of proposed data collection methods for WS2. It will gather data on: desired outcomes of gastrostomy feeding, variability in diets and reasons; use of oral feeding; perceived benefits of the alternative diets, resources associated with gastrostomy feeding and safety issues. Data will be analysed using thematic analysis. WS2 : a cohort study of 300 children who are gastrostomy fed. Data will be collected at months 0, 9 and 18 from parents, children (if appropriate) and clinicians using standardised measures and questionnaires developed specifically for the study. Data collected will include gastrointestinal symptoms, health and other outcomes (child, parent), dietary intake, anthropometry, healthcare usage, safety outcomes and resource use. Outcomes in the home-blended and formula groups will be compared using appropriate multiple regression analyses. Ethics and dissemination: The study has been approved by a research ethics committee (REC reference: 19/YH/0028). Results will be disseminated through publications and presentations for professionals and families. Study registration number: ISRCTN13977361 .